Efficacy of novel drugs hypoxia inducible factor prolyl hydroxylase inhibitor in therapy of posttransplant anemia. A review - Pawlowski, Piotr; Rybak, Julia; Bieganek, Paula; Sadłowski, Bartosz; Łukaszewicz, Stanisław; Kordialik, Jakub; Sarnacka, Sandra; Koćwin, Julia; Tokarski, Michał; Tokarska, Angelika (Quality in Sport, 2024)
Introduction The aim of our study was to evaluate the efficacy of novel drugs from the group of hypoxia-inducible factor prolyl hydroxylase inhibitors, using roxadustat as an example, in the treatment of anemia occurring in kidney recipients. In the study, we included data from recent original papers that examined the efficacy of these drugs in the treatment of post-transplant anemia. We assumed an absolute increase in hemoglobin concentration as a factor expressing the effectiveness of the therapy. Aim of the study The aim of our study was to evaluate the efficacy of novel drugs from the group of hypoxia-inducible factor prolyl hydroxylase inhibitors, using roxadustat as an example, in the treatment of anemia occurring in kidney recipients. In the study, we included data from recent original papers that examined the efficacy of these drugs in the treatment of post-transplant anemia. We assumed an absolute increase in hemoglobin concentration as a factor expressing the effectiveness of the therapy. Materials and Methods This review was conducted using publications available in databases such as PubMed, Google Scholar, Scopus and ScienceDirect. These databases were searched using keywords such as hypoxia-inducible factor prolyl hydroxylase inhibitor, roxadustat, anemia, kidney transplant, posttransplant anemia, chronic kidney disease. The time range of published articles was set to 2017-2024, and some older publications were included if they were considered to bring valuable background information necessary for understanding the issue. Articles written in English and Polish were sought; however, all publications used in this review were in English. The main reason of bias of this study may be the limited group of participants that may not be sufficiently representative, the lack of randomization in some studies, and the limited number of publications in the problem area.